Re-Opening the Silk Road to Transform Chinese Trade - Mao, Ning; McAleer, Michael (Journal of Reviews on Global Economics, 2017)
Under anti-globalization and isolationism, China is seeking to portray itself as a new leader for globalization under the banner of the Silk Road initiative. Meanwhile, China’s traditional and comparatively advantaged industry, silk, has faced dire predicaments and challenges for long time, and needs a transformation in terms of initiatives. Throughout history, the prosperity arising from silk was supposed to represent a microcosm of Chinese society. This paper searches the breakthrough point to improve the current dilemma of Chinese silk enterprises; uses a Case Study for inductive reasoning that is feasible for marketing strategies; and provides a strategy to help Chinese silk enterprises to transform their market positioning and operating modes to obtain better development opportunities. The paper also analyzes the new external environment based on the "One Belt, One Road" principle, which is of crucial importance for the implementation of new marketing strategies.